Maintaining Occupational Health: An Analysis of Fatigue and Safety Compliance in Construction Workers - Yeremia Rante Ada'; Sumardiyono; Bachtiar Chahyadhi; Reni Wijayanti; Farhana Syahrotun Nisa Suratna; Maria Paskanita Widjanarti; Rachmawati Prihantina Fauzi (Journal of Epidemiology and Public Health, 2025)
Background: Safety compliance is a critical component in preventing workplace accidents and ensuring employee well-being. Various factors may influence workers’ adherence to safety protocols, including individual characteristics such as education level and fatigue. The purpose of this study was to examine the relationships between education level, work fatigue, and safety compliance.Subjects and Method: This cross-sectional study involved 137 respondents, categorized by fatigue status. The dependent variable was safety compliance. Independent variables included work fatigue and education level. Instruments included the Fatigue Assessment Scale (FAS) questionnaire for fatigue. Data analysis utilized the chi-square test for fatigue and education levels. Results: The proportion of workers who comply with safety procedures varies across education levels, but the differences are not statistically significant. In contrast, workers with higher levels of fatigue were significantly more compliant with safety practices than those with lower fatigue..Conclusion: These findings highlight the complexity of behavioral responses to workplace demands and the need for targeted interventions.